The Primacy of EU Law: Interpretive, not Structural - Pavlos Eleftheriadis (European Papers, 2024)
(Series Information) European Papers - A Journal on Law and Integration, 2023 8(3), 1255-1291 | Article | (Table of Contents) I. Introduction. – II. Defiance. – III. Primacy of what? – IV. Pluralism in action. – V. The incoherence of pluralism. – V.1. Legal systems do not “conflict”. – V.2. Legal systems do not “overlap”. – V.3. Pluralism cannot provide a framework for consensus. – VI. Federal monism. – VII. Social monism. – VIII. Primacy: a pragmatic view. – VIII.1. Europe’s legal order. – VIII.2. MacCormick’s internationalism. – IX. Conclusion: the principle of primacy. | (Abstract) A leading position among European Union lawyers is that the primacy of EU law has a “structural” dimension. Under views known as pluralism and monism, many scholars believe that the EU has created a new legal system which either sits next to or, alternatively, above the legal systems of the member states. These views, however, are paradoxical and self-defeating. This is shown when we apply the structural theories to the question of primacy as put by the Polish Constitutional Tribunal in case K 3/21 of 7 October 2021. Neither pluralism nor monism can show that EU law prevails over a state that takes Poland’s defiant position. The correct way of understanding EU law is interpretive, not structural. It is the only way that shows that the Polish Court has acted unlawfully. The EU Treaties have not created a new “legal system”, allegiance to which remains optional. According to the best view of EU law, universally accepted in legal practice although not yet fully by legal theory, EU law is entirely continuous with the established constitutional settlement. The EU treaties are ordinary treaties of international law that create constitutional obligations in the normal way. They create bonds of cosmopolitan reciprocity that each member state is legally obliged to respect. The primacy of EU law is based on our ordinary practices concerning the status and authority of the law of nations.